Monkeys, typewriters and networks: the internet in the light of the theory of accidental excellence - Ute Hoffmann; Jeanette Hofmann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
Viewed in the light of the theory of accidental excellence, there is much to suggest that the success of the Internet and its various protocols derives from a communications technology accident, or better, a series of accidents. In the early 1990s, many experts still saw the Internet as an academic toy that would soon vanish into thin air again. The Internet probably gained its reputation as an academic toy largely because it violated the basic principles of traditional communications networks. The quarrel about paradigms that erupted in the 1970s between the telephony world and the newly emerging Internet community was not, however, only about transmission technology doctrines. It was also about the question – still unresolved today – as to who actually governs the flow of information: the operators or the users of the network? The paper first describes various network architectures in relation to the communication cultures expressed in their make-up. It then examines the creative environment found at the nodes of the network, whose coincidental importance for the Internet boom must not be forgotten. Finally, the example of Usenet is taken to look at the kind of regulatory practices that have emerged in the communications services provided within the framework of a decentralised network architecture.
Keywords: 330; Internet; Nachrichtentechnik; Kreativität